Screening of french bean (Phaseolus vulgaris L.) genotypes for high yield potential (Bangladesh Journal of Scientific and Industrial Research, 2015)
Eleven genotypes of french bean (Phaseolus vulgaris L.) were screened to select a suitable one which could provide optimum yield of fresh pod, dry seed and biochemical parameters. The maximum seed yield in french bean was found in case of genotype BB-9 (2.96 t/ha) and BARI bush bean -1 (2.95 t/ha), while that of minimum was found in BB-11(1.64 t/ha). However, maximum fresh pod yield (14.25 t/ha) was found for BARI bush bean -1, followed by BARI bush bean -2 (13.23t/ha). BARI bush bean -1 required the minimum time of 88.33 days while BB-3 the maximum of 110.00 days to attain 90% pods maturity. The highest number of diseased plants were observed in BB- 5 (30.33%) and the lowest were in BARI bush bean -1 (7.33%). No significant difference (P< 0.05) in maximum protein content among the studied genotypes was observed, for example BB-15 (21.60%) and BARI bush bean -1 (21.57%). Maximum crude fiber (5.53%) was obtained from BARI bush bean -1, followed by BB-6 (5.50%), BB-20 (5.50%) and BB-5 (5.47%), which all were statistically similar. Among all the genotypes, BARI bush bean -1 showed highest yield and superior quality of french bean. DOI: http://dx.doi.org/10.3329/bjsir.v49i4.22625 Bangladesh J. Sci. Ind. Res. 49(4), 227-232, 2014